2022
DOI: 10.1186/s12891-022-05164-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentous injury-induced ankle instability causing posttraumatic osteoarthritis in a mouse model

Abstract: Background This study aims to explore the relationship between surgically-induced ankle instability and posttraumatic osteoarthritis (PTOA) in a mouse model, and to provide reference for clinical practice. Results Ligamentectomy was performed on 24 eight-week-old male C57BL/6 J mice, which were divided into three groups. Both the anterior talofibular ligament (ATFL) and the calcaneofibular ligament (CFL) were severed in the CFL + ATFL group, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Foot (paw) print area or pressure, as one of important gait parameters involving pain, is significantly reduced in patients (mice) with ACL injury ( 25 , 45 ). The paw overlap distance, defined as the average overlapping distance of ipsilateral paws across successive strides, is significantly increased in animals with knee or ankle surgeries ( 46 ). Similarly, we found that the wound pain and knee stability affected the values of the two gait parameters, so they showed different characteristics at the early and late healing stages.…”
Section: Discussionmentioning
confidence: 99%
“…Foot (paw) print area or pressure, as one of important gait parameters involving pain, is significantly reduced in patients (mice) with ACL injury ( 25 , 45 ). The paw overlap distance, defined as the average overlapping distance of ipsilateral paws across successive strides, is significantly increased in animals with knee or ankle surgeries ( 46 ). Similarly, we found that the wound pain and knee stability affected the values of the two gait parameters, so they showed different characteristics at the early and late healing stages.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on different populations, up to 70% of patients suffering from lateral ankle sprain develop CAI (Fong et al, 2007;Swenson et al, 2009;Hiller et al, 2012). CAI has also been found to have a higher risk of developing posttraumatic osteoarthritis (Gribble et al, 2016;Liu et al, 2021;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two ankle sprain models have been developed. The first one is a mouse model by surgically transecting the CFL and ATFL (Kim et al, 2008;Kim et al, 2011;Hubbard-Turner et al, 2013;Wikstrom et al, 2015;Liu et al, 2021;Li et al, 2022). The second one is a rat model induced by manually overextending the ankle repeatedly in the plantarflexion and inversion directions (Koo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mouse models have been widely used to study various joint diseases. Inspired by mouse models with ankle instability and ankle–subtalar joint complex instability, as well as our team's existing techniques and previous research experience [ 16 , 17 ]. We believed that this problem of establishing a mouse model of PTOA caused by subtalar joint instability may be investigated via a similar approach.…”
Section: Introductionmentioning
confidence: 99%